The potential contribution of cymene isomers to insecticidal and repellent activities of the essential oil from Alpinia zerumbet. (February 2021) - Feng, Yi-Xi; Zhang, Xu; Wang, Yang; Chen, Zhen-Yang; Lu, Xin-Xin; Du, Yue-Shen; Du, Shu-Shan
Abstract: In this work, the essential oils (EOs) of Alpinia zerumbet (Pers.) Burtt. et Smith were extracted from different organs (stems, leaves, flowers and fruits). The GC-MS analysis showed that two isomers m-cymene and o-cymene distributed totally diverse among different organs: m-cymene were relatively rich in the EOs from stems, flowers and fruits (7.1, 11.3 and 6.6%, respectively), but absent in the EO from leaves; o-cymene was predominant in the EO from leaves (14.9%), but missing in the EOs from other organs. A. zerumbet EOs from different organs, as well as seven characteristic compounds (m-cymene, o-cymene, camphene, eucalyptol, linalool, camphor, and borneol) showed varying degrees of insecticidal and repellent activities to Tribolium castaneum and Liposcelis bostrychophila . o-Cymene exhibited stronger fumigant and contact toxicity than m-cymene did to both insect species, suggesting that the relative position of methyl and isopropyl on benzene ring would influence the insecticidal activity. Positive correlation between relative content of camphor and LC50 value to T. castaneum was significant, while fumigant and contact toxicity of EOs appeared to be negatively correlated with the content of m-cymene. Graphical abstract: Image 1 Highlights: The essential oils (EOs) of Alpinia zerumbet with regard of organs were extracted and analyzed by GC-MS. Two cymene isomers were identified in EOs, and showed totally inverse distribution manners in EOs from different organs. The EOs from leaves showed the strongest fumigant and contact toxicity to both T. castaneum and L. bostrychophila. The fumigant and contact toxicity of o-cymene were stronger than that of m-cymene. The fumigant and contact toxicity of EOs appeared to be negatively correlated with the content of m-cymene.